Sarcopenia remaining after intensive nutritional feeding support could be a criterion for the selection of patients for surgery for oesogastric junction adenocarcinoma. Issue 2 (February 2023) - de Mathelin, Pierre; Manfredelli, Simone; Delhorme, Jean-Baptiste; Venkatasamy, Aina; Rohr, Serge; Brigand, Cécile; Gaiddon, Christian; Romain, Benoît
Abstract: Background: Sarcopenia is recognized as a negative prognostic factor in several cancers. The aim of this study was to investigate the impact of nutritional support with feeding jejunostomy (FJ) on the occurrence of sarcopenia and how it may affect postoperative short-term outcomes and long-term survival outcomes in patients undergoing esophagectomy for oesogastric junction adenocarcinoma (OJA). Methods: Patients with OJA were included. The presence of sarcopenia was determined using cutoff values of the total cross-sectional muscle tissue measured on CT scan. We analyzed risk factors for sarcopenia occurrence and the impact of preoperative sarcopenia on postoperative results, overall survival and disease-free survival. Results: A total of 124 patients were eligible for analysis. Ninety-one patients underwent surgery after chemotherapy, and 72 of them received preoperative FJ. Among the 91 patients, 21 patients (23.0%) were sarcopenic after preoperative chemotherapy. Multivariate analysis showed that FJ is a protective factor against sarcopenia occurrence. Overall survival was significantly different between sarcopenic and nonsarcopenic patients (median survival = 33.7 vs. 58.6 months, respectively, p = 0.04), and sarcopenia occurrence was an independent risk factor for overall survival in patients who underwent surgery (HR = 3.02; CI 95% 1.55–5.9; p < 0.005). Subgroup analyses showed no differences in overall survival between patients who presented sarcopenia despite nutritional prehabilitation with a FJ and patients excluded from surgery in palliative situations (median survival = 21.9 vs. 17.2 months, respectively, p = 0.46). Conclusion: The persistence of sarcopenia after preoperative chemotherapy despite renutrition with FJ could be a selection factor to propose curative surgery for OJA. Highlights: Sarcopenia is recognized as a negative prognostic factor in several cancers. Prehabilitation with nutritional support with feeding jejunostomy is a protective factor for sarcopenia occurrence in patients with esogastric junction adenocarcinoma. Sarcopenia occurrence was an independent risk factor for overall survival in patients who underwent surgery. Overall survival was similar between sarcopenic patients after nutritional prehabilitation with a FJ and patients excluded from surgery in palliative situations. The persistence of sarcopenia despite renutrition program could be a selection factor for surgery.